1965
DOI: 10.2118/1126-pa
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Domes Unit Carbonated Waterflood - First Stage

Abstract: Carbonated water has been injected as a slug, followed by non-carbonated water, in the Bartlesville sand formation of the Domes unit in northeastern Oklahoma. Initial results are shown for the first stage of the flood, consisting of nine enclosed five-spots comprising 132 acres. Production history indicates the carbon dioxide have been transferred to the residual oil and has mostly been retained in the reservoir. A large portion of the formation is apparently being bypassed due to stratification and reservoir … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…About 5,000 tons of carbon dioxide was injected (Scott and Forrester, 1965). Before initiation of CWI, each well was treated with 500 gallons of propane and 25 gallons of detergent.…”
Section: Dome Projectmentioning
confidence: 99%
See 1 more Smart Citation
“…About 5,000 tons of carbon dioxide was injected (Scott and Forrester, 1965). Before initiation of CWI, each well was treated with 500 gallons of propane and 25 gallons of detergent.…”
Section: Dome Projectmentioning
confidence: 99%
“…Source: Scott and Forrester (1965) Production rate responded quickly to injection of carbonated water. In November 1961, oil production climbed to 448 BOPD.…”
Section: Figure 8 History Of Dome Unit Pilotmentioning
confidence: 99%
“…It was found that CWI could produce approximately 43 % more oil than waterflooding and would also improve water injectivity and mobility ratio . Another field program was in the Domes Unit in 1965 . It was estimated that the slug injection of carbonated water and unadulterated water yielded about 9 % additional oil recovery.…”
Section: Introductionmentioning
confidence: 99%
“…[20,21] Another field program was in the Domes Unit in 1965. [22] It was estimated that the slug injection of carbonated water and unadulterated water yielded about 9 % additional oil recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Another field application of carbonated water was in the Domes Unit 17) . The carbonated water injection started in 1961, followed by the primary development phase, in which the cumulative oil production was 1,225,000 bbl from the total unit area while using a water injection scheme.…”
mentioning
confidence: 99%